Genotypic and ecological variability of zinc content in the grain of spring bread wheat varieties in the international nursery KASIB - V. P. Shamanin; P. Flis; T. V. Savin; S. S. Shepelev; O. G. Kuzmin; A. S. Chursin; I. V. Pototskaya; I. E. Likhenko; I. Yu. Kushnirenko; A. A. Kazak; V. A. Chudinov; T. V. Shelaeva; et al. (Вавиловский журнал генетики и селекции, 2021)
Spring bread wheat is the staple crop in Western Siberia and Kazakhstan, a significant portion of which goes for export. Wheat breeding with a high level of zinc in wheat grain is the most cost-effective and environmentally friendly way to address zinc deficiency in the diet. The purpose of this work was to evaluate the contribution of the factors ‘location’ and ‘genotype’ in the variability of zinc content in wheat grain, and to identify the best varieties as sources of this trait for breeding. The research on screening zinc content in the wheat grain of 49 spring bread wheat varieties from the KazakhstanSiberia Spring Wheat Trial (KASIB) nursery was carried out at 4 sites in Russia (Chelyabinsk, Omsk, Tyumen, Novosibirsk) and 2 sites in Kazakhstan (Karabalyk and Shortandy) in 2017–2018. The content of zinc in wheat grain was evaluated at the Ionomic Facility of University of Nottingham in the framework of the EU project European Plant Phenotyping Network-2020. The analysis of variance showed that the main contribution into the general phenotypic variation of the studied trait, 38.7 %, was made by the factor ‘location’ due to different contents of zinc and moisture in the soil of trial sites; the effect of the factor ‘year’ was 13.5 %, and the effect of the factor ‘genotype’ was 8.0 %. The most favorable environmental conditions for accumulation of zinc in wheat grain were observed in the Omsk region. In Omsk, the average zinc content in all studied varieties was 50.4 mg/kg, with 63.7 mg/kg in the best variety ‘OmGAU 100’. These values are higher than the target values of the international program Harvest Plus. ‘Novosibirskaya 16’ (49.4 mg/kg), ‘Silach’ (48.4 mg/kg), ‘Line 4-10-16’ (47.2 mg/kg), ‘Element 22’ (46.3 mg/kg) and ‘Lutescens 248/01’ (46.0 mg/kg) were identified as being the best varieties. Significant possibilities for the production of wheat grain with high zinc content, which is in demand for the production of bread and pastry products with functional properties, were identified in the Western Siberian region.